Association of metabolic syndrome with depression in US adults: A nationwide cross-sectional study using propensity score-based analysis - Zhang, Li; Zhou, Quan; Shao, Li Hua; Hu, Xue Qin; Wen, Jun; Xia, Jun (Frontiers in Public Health, 2023)
Background: Association of metabolic syndrome (MetS) with depression has been previously reported, however they come out with ambiguous results due to imbalanced confounding factors. Propensity score based analysis is of great significance to minimize the impact of confounders in observational studies. Thus, the current study aimed to clarify the influence of MetS on depression incidence in the U.S. adult population by using propensity score (PS)-based analysis. Methods: Data of 11,956 adults aged 20-85 years from the National Health and Nutrition Examination Survey (NHANES) database between 2005 to 2018 was utilized. Using a 1:1 PS matching (PSM), the present cross-sectional study included 4,194 participants with and without MetS. Multivariate logistic regression model and three PS-based methods were applied to assess the actual association between MetS and depression incidence. Stratified analyses and interactions were performed based on age, sex, race, and components of MetS. Results: After PSM, MetS patients increased by 40% risk of getting depression in PS-adjusted model (OR=1.40, 95% confidence interval [CI]: 1.202-1.619, P＜0.001), and we could still observe the positive association in fully-adjusted model (OR=1.37, 95% CI: 1.172-1.596, P＜0.001). Regarding the count of MetS’ components, having 4 and 5 conditions significantly elevated the risk of depression both in PS-adjusted model (OR=1.78, 95% CI: 1.341-2.016, P＜0.001 versus OR=2.11, 95% CI: 1.626-2.699, P＜0.001) and in the fully-adjusted model (OR=1.56, 95 CI%: 1.264-1.933, P＜0.001 versus OR=1.90, 95% CI: 1.458-2.486, P＜0.001). In addition, an elevation in MetS components' count was associated with a significant linear elevation in the mean score of PHQ-9 (F =2.8356, P <0.001). In the sensitivity analysis, similar conclusions were reached in both the original and weighted cohorts. Further interaction analysis revealed a clear gender-based difference in the association between MetS and depression incidence. Conclusion: MetS exhibited a greatest influence on depression incidence in U.S. adults, supporting the necessity of early detection and treatment of depressive symptoms in MetS patients (or its components), particularly in female cases.